2001
DOI: 10.1103/physrevb.63.125424
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-induced changes of the local structure in Fe/V (001) superlattices

Abstract: We determined the changes of the local structure of the V layers in a single-crystal Fe͑3 ML͒/V͑13 ML͒ ͑001͒ superlattice upon loading with hydrogen using Extended X-ray Absorption Fine Structure ͑EXAFS͒. Going from V to VH 0.5 , the initial bct structure is strongly distorted and resembles the local structure of bulk ␤-V hydride. The obtained out-of-plane lattice parameter is a sequence of 3.18 Åϩ(Ϫ1) i 0.41 Å, i ϭ0,1,2, . . . , yielding a lattice expansion of 7.3%. The resulting average expansion of the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
(28 reference statements)
2
13
0
Order By: Relevance
“…29,30 This latter type of insertion has been described as unstable against a phase transition toward the ␤ phase of vanadium according to EXAFS data. 13 We note that in this ␤ phase of V 2 H the O site is highly distorted, being the H atom no longer aligned with the V atoms in the plane. Such local structure resembles the triangular configuration obtained as the ground state in the H-loaded V dimer.…”
Section: Bulk Environmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…29,30 This latter type of insertion has been described as unstable against a phase transition toward the ␤ phase of vanadium according to EXAFS data. 13 We note that in this ␤ phase of V 2 H the O site is highly distorted, being the H atom no longer aligned with the V atoms in the plane. Such local structure resembles the triangular configuration obtained as the ground state in the H-loaded V dimer.…”
Section: Bulk Environmentsmentioning
confidence: 98%
“…The vanadium layers are also suggested to undergo a structural phase transition to the ␤ phase of vanadium hydride as increasing the H content, according to the extended x-ray absorption fine structure ͑EXAFS͒ data. 13 On the theoretical side concerning Fe/V systems, most of the studies have focused on the magnetic profiles in multilayers, 14,15 and few of them have considered the presence of H. Ostanin et al 16 using full-potential linear muffintin orbital ͑FP-LMTO͒ studied the magnetic behavior at the interface and the resistivity as a function of the H concentration in the V layer. The moment at the interface is supposed to decrease due to the important tetragonal distortion subsequent to the H absorption, although structural relaxation was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…7 The difference in H -H interaction energies is probably caused by a different interstitial site occupancy, i.e., T in case of biaxial tensile strain and O z in case of biaxial compressive strain. 8 This is not unreasonable considering that the site occupancy in V is very sensitive to applied strain. 9 For Fe/ V it means that the in-plane compression of the V layers and the corresponding elongation of the out-ofplane axis open up the lattice for population of the O z sites.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, here we find that a modification of the V lattice volume of 5% corresponds to a change of resistivity by approximately a factor of 10. Recently, Burkert et al 12 found that the average expansion of the out-of-plane lattice parameter of V in Fe/ V multilayers loaded with 50% H is close to 5%. They also found that the in-plane lattice parameter was not modified by H loading, leading to a volume expansion close to 5%.…”
Section: Resultsmentioning
confidence: 99%